Aplikasi NotaryReq Untuk Manajemen Data Layanan Notaris Menggunakan Metodologi Prototyping - Muhtar Muhtar; Handrie Noprisson (JSAI (Journal Scientific and Applied Informatics), 2025)
This research aimed to develop a web-based data management application for notary/PPAT administration at the Notary and PPAT Office of H. Arief Afdal, SH, M.Kn., located in South Jakarta. The software engineering approach used in this study was the prototyping method, where system development was conducted iteratively based on direct user feedback. The research took place from April to June 2024. The system design utilized Unified Modeling Language (UML) with the help of Modelio version 4.1 software. The application was developed using PHP for the backend, JavaScript for the frontend, along with Visual Studio Code and Laragon as the development environment. The developed notary/PPAT data management application included various features with actors such as clients, notary staff, financial staff, and administrators. Clients could submit, verify, and manage request data and payments, while notary staff were responsible for verifying requests, managing various administrative books such as the ledger, land books, and legalization books, as well as monitoring audit logs. Financial staff verified payment data, and administrators had full access to manage all request data, payments, and other administrative books, ensuring data accuracy and monitoring transparency through audit log features.